2003
DOI: 10.1046/j.1365-2559.2003.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma in older patients: clinicopathological analysis of 32 cases with emphasis on unusual histological features

Abstract: Less than 10% of synovial sarcomas occur in patients over 60, in which age group this diagnosis is often not considered. Despite inevitable bias in consultation material, it seems that these cases, when compared with younger age groups, more often show poorly differentiated histology and more often develop at unusual locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…1e). Reportedly, biphasic synovial sarcomas may display distinct papillary structures [19][20][21]. However, the bland nuclear features, lack of mitotic figures (and corresponding low proliferative activity in the immunohistochemical study) and the strong and diffuse positivity for cytokeratins in the spindle cells in the actual tumor would be highly unusual for a SS which typically displays a weak and/or patchy cytokeratin positivity in the spindle cell component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1e). Reportedly, biphasic synovial sarcomas may display distinct papillary structures [19][20][21]. However, the bland nuclear features, lack of mitotic figures (and corresponding low proliferative activity in the immunohistochemical study) and the strong and diffuse positivity for cytokeratins in the spindle cells in the actual tumor would be highly unusual for a SS which typically displays a weak and/or patchy cytokeratin positivity in the spindle cell component.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005 Carrizo and Luna presented 2 cases of LGPACNP with nuclear positivity for thyroid transcription factor-1 (TTF-1) [2]. Based on this immunohistochemical feature (and the positivity for cytokeratin 19) in conjunction with the histological characteristics (papillarity, psammoma bodies, neoplastic cells with overlapping nuclei and clear chromatin), the authors coined the term ''thyroid-like nasopharyngeal papillary adenocarcinoma'', which has been used by subsequent investigators. Given the similarities between LGPACNP (especially those with nuclear expression of TTF-1) and papillary thyroid carcinoma (PTC), we also undertook a molecular genetic study regarding the mutational status of the BRAF-gene.…”
Section: Introductionmentioning
confidence: 99%
“…The other differential diagnosis is leiomyosarcoma which have cigar-shaped nuclei with perinuclear vacuoles, however, they are almost always CK AE1/AE3 and EMA negative and desmin and actin positive [20]. Malignant solitary fibrous tumor shows stag-horn shaped vasculature with ropy collage, and usually positive for CD34 and BCL-2; however, it is usually negative for CD99 and CK AE1/AE3.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 10% of synovial sarcomas occur in patients over 60 years. Chan et al [6] analyzed 32 patients older than 60 years with synovial sarcoma. They concluded that the tumors in this age group occur more often in unusual locations and have more often poorly differentiated morphology.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly apparent, however, that synovial sarcomas may arise in a wide variety of other sites, including head and neck, mediastinum, heart, kidney, prostate, esophagus and vulva, and that they also occur in elderly patients [6]. There are four different morphological subtypes of synovial sarcoma: biphasic, monophasic spindle cell type, monophasic glandular type and poorly differentiated.…”
Section: Introductionmentioning
confidence: 99%